Case Report: Another Burden to Bear: The Impacts of Climate Change on Access to Sexual and Reproductive Health Rights and Services in Bangladesh - Husaini, Sediqa; Davies, Sara E. (Frontiers in Climate, 2022)
Climate change poses significant threats to humans and the environment. Climate-related events, such as extreme weather events, droughts, rising sea levels, leave millions vulnerable. The sexual and reproductive health and rights (SRHR) of women are increasingly negatively impacted during and post-climate change-related events. In the absence of climate-related events, access to SRHR services may already be limited due to economic, cultural and social constraints that prevent women from making decisions concerning their bodily autonomy. During and post climate disasters, these access constraints increase. Limited access to SRHR services increase women’s risk of physical, mental, and psychological harm; it also impacts their ability to build capacity and resilience to climate change. This article examines the rise in climate-related events in Bangladesh and the corresponding harm of climate change on women’s access to sexual and reproductive health care. The article argues that the impact of climate change on women needs to be viewed through a reproductive justice framework. The first step to prevent the gendered impacts of climate change is for international and national frameworks to identify individual needs to build capacity and resilience.